IMPLEMENTASI PENDEKATAN HUMANISTIK DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM UNTUK MENUMBUHKAN NILAI-NILAI KEMANUSIAAN - Fahira, Ade; Hamami, Tasman; Saripudin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The curriculum is a tool for achieving educational goals as well as a guideline for implementing teaching in all types of education. In a humanistic context, the curriculum is not only seen as a set of plans and programs, but also as a means to develop individual potential as a whole. The curriculum is the main component of education and also a compass for where students will be taken. The curriculum must be developed and aligned to suit current developments, so that it can facilitate educational programs in order to realize the achievement of national education goals that are enshrined in law. This research aims to examine the humanistic approach in developing the Islamic Religious Education curriculum. This research uses library research by taking data from library sources such as articles, books, documents and others. The results of this research show that the Islamic religious education curriculum with a humanistic approach can be applied in Indonesia in an effort to develop students' potential and foster human values. The humanistic approach views individuals as beings who have freedom, a desire to develop, and can reach their full potential through experience and self-understanding. In this case, it shows that every student has the capacity to develop their life in a way that they can do themselves.